Microbial corrosion of galvanized steel by a freshwater strain of sulphate reducing bacteria (Desulfovibrio sp.) - Ilhan-Sungur, E.; Cansever, N.; Cotuk, A. (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Microbially influenced corrosion of galvanized steel was investigated exposing coupons (2.0 x 2.0 cm) to culture of sulphate reducing bacteria strain Desulfouibrio sp. The coupons were exposed to the SRB culture for 4, 8, 24, 72, 96, 168, 360 and 744 h along with a control set in uninoculated medium. The results from the present study suggest that SRB were responsible for the corrosion of the galvanized steel. The corrosion rate of galvanized steel was not be correlated with the number of sessile SRB cells. Also Desulfouibrio sp. had an ability to produce EPS (Extracellular Polimeric Substances) and biodegrade the carbohydrate, that is the predominant component of the EPS produced by them. When Desulfovibrio sp. cells were in logarithmic phase, the concentration of dissolved zinc in the bulk solution was very toxic for Desulfooibrio desulfuricans. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: galvanized steel; zinc; EPS; microbial corrosion; SRB; Materials Science; Metallurgy & Metallurgical Engineering